Teknik Budidaya Microgreen Berbasis Varietas Tanaman Lokal - Sarjani, Alvita Sekar; Endrawati, Tri; Puspitorini, Palupi (AJAD : Jurnal Pengabdian kepada Masyarakat, 2024)
The increase in population density has driven innovations in limited-space gardening, known as urban farming, which is gaining popularity among urban residents and millennials due to its support for a healthy lifestyle emphasizing the consumption of nutritious, pesticide-free vegetables. One prominent technique in urban farming is the cultivation of microgreens. Microgreens are edible young plants harvested within 7-21 days after germination, and they contain significantly higher nutritional levels compared to mature vegetables, with additional benefits such as cardiovascular disease prevention and cholesterol metabolism regulation. Although microgreens are popular in developed countries, this technique has yet to become a trend in Blitar. Therefore, this program aims to introduce microgreen cultivation using local plant varieties in Blitar. The training, conducted in Rejowinangun Village, involved 20 members of a women farmers' group and included both theoretical and practical components, from preparing the growing media to harvesting. The training successfully enhanced participants' knowledge and skills, opening up economic opportunities through the high-value marketing of microgreens. Additionally, the use of limited space for growing microgreens proved effective in meeting family nutritional needs and optimizing available resources.